Future European Alliance - Europe as a Flexible Democracy - Bruno S. Frey; Armin Steuernagel; Jonas Friedrich (Center for Economic Studies and ifo Institute (CESifo), 2018)
A reasonable future for Europe can only be achieved if two essential elements are fulfilled: Firstly, newly established institutions must be democratic and have strong support from citizens rather than from national governments. Secondly, the large number of different ethnic, cultural, religious, and regional units existing on the European continent must be able to maintain their identity. This diversity must be institutionally supported rather than be undermined by standardization and centralization. We suggest political institutions, which are formed to meet these goals, following the example of Functional, Overlapping, Competing Jurisdictions (FOCJ). If these two goals are adequately reached, a future alliance raises the identification with the European project, and induces citizens to exhibit civic virtue in strengthening these goals.
Keywords: H10; H40; K33; P40; P48; R10; 330; europe; flexible institutions; identity; diversity; FOCJ; European Union